2019
DOI: 10.1088/1361-6528/ab36f4
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of orally administered ZnO:Eu nanoparticles through the blood–testis barrier: the effect on kinetic sperm parameters and apoptosis in mice testes

Abstract: Zinc-based nanoparticles are promising materials for various applications, including in biomedicine. The aim of our study was to determine the effect of fluorescent europium-doped zinc oxide nanoparticles (ZnO:Eu NPs) on sperm parameters, cell apoptosis and integrity of the blood–testis barrier (BTB) in mice. Nanostructures were orally administered to adult mice (n = 34). Animals were sacrificed after 3 h, 24 h, 7 d and 14 d following oral administration. Sperm was collected and analysed for viability and kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…), route of administration and dose may strongly affect their behavior in the organism. Our previous studies reported efficient absorption of orally administered, zinc-based nanoparticles [ 33 , 34 , 35 , 36 ]. Hilty et al also reported that nanosized Fe/Zn compounds presented higher bioavailability, compared to standard FeSO 4 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), route of administration and dose may strongly affect their behavior in the organism. Our previous studies reported efficient absorption of orally administered, zinc-based nanoparticles [ 33 , 34 , 35 , 36 ]. Hilty et al also reported that nanosized Fe/Zn compounds presented higher bioavailability, compared to standard FeSO 4 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZnO:Fe nanoparticles were prepared using microwave hydrothermal technique [ 33 , 34 , 35 , 36 ]. Two starting compounds as the iron ions source were used to obtain two kinds of samples: ZnO:Fe containing only Fe 3+ ions and ZnO:Fe 3+ enriched with Fe 2+ ions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sundarraj et al [90] observed the accumulation of NPs in the testis of mice after iron oxide NP (25 and 50 mg/kg) exposure, documenting the ability of these NPs to cross the BTB and accumulate in the testicular tissue as demonstrated by the presence of iron content. Oral administration of fluorescent europium doped ZnO NPs to mice for 14 days showed their accumulation in testes, indicating the penetration of these NPs through the BTB [91]. Similarly, after intragastric administration of TiO2 NPs at the concentration of 2.5, 5 and 10 mg/kg BW in male mice for 90 days, it was observed that NPs crossed the BTB, reached the testes and then accumulated, inducing testicular toxicity resulting in poor quality of sperm, changes in hormone level and testicular lesions [92].…”
Section: Path Of Nps Into the Reproductive Systemmentioning
confidence: 99%
“…These effects are as reduction and loss of cells in seminiferous tubules in testicular tissue. In fact, these nanoparticles are able to degenerate and decrease cell types in the seminiferous tubules (such as spermatogonia, primary spermatocyte, spermatid and sperm cells), outer part of the tubules (such as leydig, fibroblast cells and blood vesicles), seminiferous epithelium and tubule are diameters (128).…”
mentioning
confidence: 99%